Implementasi Kebijakan Pemerintahan Desa dalam Meningkatkan Usaha Mikro Kecil dan Menengah di Desa Laut Dendang Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Nasution, Ira Nirwana; Lubis, Khairunnisah (Al-DYAS, 2025)
This study aims to analyze the implementation of village government policies in supporting the development and empowerment of Micro, Small, and Medium Enterprises (UMKM) through the Village-Owned Enterprise (Badan Usaha Milik Desa/BUMDes) Bumi Pertiwi in Laut Dendang Village, Percut Sei Tuan Subdistrict, Deli Serdang Regency. The background of this study is the high number of UMKM actors in the village and the existence of village policies aimed at strengthening the local economic sector. This research employed a descriptive qualitative approach with data collected through in-depth interviews, observation, and document analysis. The results indicate that the implementation of BUMDes programs in supporting UMKM has not been optimal due to several obstacles, including delays in loan repayments caused by low borrower discipline, weak recipient selection systems, limited program outreach, and inadequate managerial and administrative capacity of BUMDes managers. These obstacles have affected the effectiveness of the program and led to declining community trust in BUMDes. Nevertheless, BUMDes still holds potential as an instrument for strengthening the village economy if accompanied by continuous capacity building, improved governance, strict selection systems, and enhanced human resource capacity. These findings contribute to the strengthening of community-based local economic institutions and support sustainable village development.